Numerical simulation of gas dynamic and physical-chemical processes in hypersonic flows past bodies - Volkov, K.N.; Emelyanov, V.N.; Karpenko, A.G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2017)
Numerical simulation of gas dynamic and physical-chemical processes in hypersonic flows past bodies of various shapes is considered. The mathematical model includes the gas dynamics equations of real gases and the equations of chemical kinetics describing equilibrium processes in high-temperature air. The finite volume method and various finite difference schemes for the discretization of convective fluxes are used to discretize the governing equations. The capabilities of the numerical procedure are demonstrated by the solution of a number of problems in physical-chemical gas dynamics. The calculations are performed using general-purpose graphics processor units. The computational time achieved with the use of various finite difference schemes and the approaches to describe the properties of high-temperature air are discussed.